2011
DOI: 10.1051/0004-6361/201015821
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopic variability of Herbig Ae/Be stars

Abstract: Aims. In order to gain insights into the variability behaviour of the circumstellar (CS) atomic gas, we have analysed 337 multi-epoch optical spectra of 38 Herbig Ae/Be (HAeBe) stars. Methods. Equivalent widths (EWs) and line fluxes of the Hα, [O i]6300, He i5876 and Na iD lines were obtained for each spectrum; the Hα line width at 10% of peak intensity (W 10 ) and profile shapes were also measured and classified. The mean line strengths and relative variabilities were quantified for each star. Simultaneous op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 45 publications
14
92
2
1
Order By: Relevance
“…has been observed in several young objects: variations affect in particular the line profiles, but the line flux changes at maximum by a factor of a few, which is much less than variations observed on longer timescales (e.g. Scholz et al 2005;Stelzer et al 2007;Mendigutía et al 2011). Apart from this limitation, the accretion luminosities derived from the five tracers should therefore be consistent with each other.…”
Section: Emission Lines As Accretion Tracersmentioning
confidence: 83%
“…has been observed in several young objects: variations affect in particular the line profiles, but the line flux changes at maximum by a factor of a few, which is much less than variations observed on longer timescales (e.g. Scholz et al 2005;Stelzer et al 2007;Mendigutía et al 2011). Apart from this limitation, the accretion luminosities derived from the five tracers should therefore be consistent with each other.…”
Section: Emission Lines As Accretion Tracersmentioning
confidence: 83%
“…All kinds of shapes from the classification by Reipurth et al are observed: P Cygni, single-and doublepeaked (see, e.g., Böhm & Catala 1995;Grinin et al 2001;Mora et al 2001;Feigelson et al 2003;Beskrovnaya & Pogodin 2004;Movsessian et al 2008;Grady et al 2011;Montesinos 2009;Mendigutía 2012). Such a vast sample of profile shapes suggests that this line originates in a very complex environment possibly including the accretion disk, disk wind, jet, and magnetosphere.…”
Section: Hybrid Model: Disk Wind X-wind and Magnetospherementioning
confidence: 93%
“…There are at least three possible types of outflows around young stellar objects: (1) a disc wind launched from the accretion disc (e.g. Blandford & Payne 1982;Ustyugova et al 1995;Romanova et al 1997;Ouyed & Pudritz 1997; Ustyugova Grady et al (1996), h Mendigutía et al (2011), i van Leeuwen (2007), j Perryman et al (1997), k Cutri et al (2003).…”
Section: Introductionmentioning
confidence: 99%